High-performance acrylic coating and preparation method thereof
By modifying graphene oxide with silane coupling agent and copolymerizing with hydroxyacrylate monomers to form a composite emulsion, the lack of performance of traditional acrylic coatings under extreme climatic conditions is solved, and the mechanical properties and weather resistance of the coatings are significantly improved.
Patent Information
- Application Number
- CN202510352673.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional acrylic coatings are difficult to meet the high standards for long-term use under extreme climate conditions, and show shortcomings in weather resistance, waterproofing, mechanical properties and chemical resistance.
Unsaturated silane coupling agent is used to modify graphene oxide to produce saturated silicone modified graphene oxide, and then copolymerize with hydroxyacrylate monomer to form a composite emulsion to improve the mechanical properties and weather resistance of the coating.
It significantly improves the impact resistance, wear resistance, water resistance and chemical resistance of acrylic coatings, extends the service life of the coating, and reduces environmental pollution.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of acrylic coatings, and in particular to a high-performance acrylic coating and a preparation method thereof. Background Art
[0002] Acrylic paints have been widely used in the construction and industrial fields as a protective and decorative coating widely used on a variety of surfaces such as building exteriors, bridges, and vehicles. Acrylic resin is the key ingredient, which gives the paint good adhesion, flexibility, weather resistance, and chemical resistance. Acrylic paints are favored for their excellent outdoor durability and color stability. They can effectively protect buildings from environmental factors such as ultraviolet rays, acid rain, and moisture, thereby extending the service life of buildings. In addition, acrylic paints also have good air permeability, which can allow moisture inside the building to escape, avoiding damp and moldy walls while keeping the interior of the building dry and comfortable.
[0003] Although acrylic coatings have many advantages, they still face some challenges in practical applications, especially in extreme climate conditions such as high temperature, strong ultraviolet radiation, frequent temperature changes, etc. The performance of traditional acrylic coatings often cannot meet the high standards required for long-term use. These problems not only affect the performance and life of the coating, but may also have adverse effects on the structural safety of the building and the environment.
[0004] First, acrylic paints are prone to chalking, fading, and cracking when exposed to UV light for a long time. UV radiation can damage the polymer chains in the coating, causing the coating to deteriorate. This phenomenon is particularly evident in environments with high temperatures and strong UV radiation. In addition, frequent temperature changes can cause the coating to expand and contract repeatedly, which can generate stress and eventually cause the coating to crack or peel off. These weathering issues not only affect the aesthetics of the building, but may also reduce the building's protective effect and shorten its service life.
[0005] Secondly, the waterproof performance of traditional acrylic coatings is limited. Especially in rainy or humid areas, moisture can easily penetrate into the coating, causing blistering, peeling, and even corrosion of the substrate. Prolonged immersion in water or frequent contact with water can soften the coating and reduce its protective performance. This moisture penetration problem not only affects the appearance of the coating, but also accelerates the aging of the coating, further reducing its weather resistance and durability.
[0006] In addition, the mechanical properties of acrylic coatings, such as impact resistance and abrasion resistance, are generally inferior to those of solvent-based coatings. In the event of external impact or abrasion, the coating is easily damaged, affecting its protective function. Especially in areas with heavy traffic, such as parking lots and sidewalks, acrylic coatings have poor abrasion resistance and are easily worn and damaged. This lack of mechanical properties limits its application in some high-demand application scenarios.
[0007] When acrylic coatings are exposed to corrosive substances such as acid rain and industrial pollutants for a long time, the coating is easily corroded, resulting in performance degradation. This problem is particularly serious in industrial areas or coastal areas. The corrosive substances in acid rain and industrial pollutants can destroy the chemical structure of the coating, causing the coating to fail. In addition, certain solvents can also dissolve or soften acrylic coatings, affecting their protective effect. This problem of chemical resistance not only affects the life of the coating, but may also threaten the structural safety of the building. In addition, traditional acrylic coatings may release volatile organic compounds during production and use, which has an adverse effect on human health and the environment. With the increasingly stringent environmental regulations, the development of low-VOC or VOC-free environmentally friendly coatings has become a trend in the development of the industry. Coatings with high VOC content not only pose a threat to the health of construction workers and residents, but also pollute the atmospheric environment and aggravate problems such as the greenhouse effect. Acrylic coatings have high requirements for the surface of the substrate. If the surface of the substrate is not properly treated, such as the presence of impurities such as oil, dust, or improper humidity and temperature control, it may lead to poor coating adhesion and affect the final coating effect. In addition, acrylic paint is very sensitive to the temperature and humidity of the construction environment. Improper environmental conditions will affect the drying and curing process of the paint, thereby affecting the quality of the coating. These construction condition restrictions increase the difficulty of construction, increase construction costs, and affect the popularity and application of paint.
[0008] In summary, although acrylic coatings are widely used in building exterior walls and other fields, their shortcomings in weather resistance, waterproof performance, mechanical properties, chemical resistance, etc. limit their application in a wider range of fields. These problems not only affect the performance and life of the coating, but may also have an adverse effect on the structural safety and environment of the building. Therefore, the development of a highly weather-resistant and high-performance acrylic coating has become a problem that needs to be solved urgently. Summary of the invention
[0009] In order to solve the problem that the waterproof and mechanical properties of acrylic coatings in the prior art do not meet the requirements for use on building exterior walls, the present application provides a high-performance acrylic coating and a preparation method thereof, wherein graphene oxide is modified by an unsaturated silane coupling agent to obtain saturated silicone-modified graphene oxide, which is then copolymerized with hydroxyl acrylate monomers to obtain a composite emulsion. The prepared composite emulsion has high stability and mechanical properties that are superior to traditional water-based high-hydroxyl value polyacrylates.
[0010] The present application provides a method for preparing a high-performance acrylic coating, comprising the following steps:
[0011] S1. After mixing graphite and sodium nitrate, slowly add concentrated sulfuric acid, then place in an ice-water mixture and stir, slowly add potassium permanganate and stir at 33-37°C for 8-10h, then add deionized water, slowly stir and drop hydrogen peroxide until the solution turns golden yellow, then let stand for 8-12h, then filter the solution, wash with hydrochloric acid until the pH of the solution is 5-7, then wash the solution with deionized water and dry to obtain graphene oxide;
[0012] S2, adding deionized water to the graphene oxide obtained in S1 and mixing evenly, adding a silane coupling agent to anhydrous ethanol to dissolve, and then adding it to the aqueous solution of graphene oxide, followed by ultrasonic treatment and stirring; adding hydrochloric acid and adjusting the pH to 5-7, reacting in a 48-52°C water bath for 1-2 hours, then heating to 70-80°C and continuing the reaction for 1-2 hours, finally cooling to room temperature, centrifuging, washing, and drying to obtain organosilicon-modified graphene oxide;
[0013] S3, mixing initiator BPO and 1-methoxy-2-propanol and heating to 100-120°C, adding a chain transfer agent, and then dripping a mixed solution of methyl methacrylate, acrylic acid, hydroxyethyl methacrylate, and styrene, dripping within 3 hours, keeping warm for 0.5h-1h, then adding the organosilicon-modified graphene synthesized in S2 at 100-120°C, and then keeping warm for 1.5-2h, cooling to 65-70°C, adding triethanolamine to react for 20-40min, and then adding deionized water to disperse to obtain an acrylic coating;
[0014] S4. Apply the acrylic paint obtained in S3 onto a polytetrafluoroethylene film-forming plate, and then dry it at room temperature for 5-7 days to form a film naturally, and put it into an oven and dry it at 50-60° C. for 36-48 hours to form a film.
[0015] Furthermore, in step S1, the mass ratio of graphite to sodium nitrate is 1:1 to 5:1.
[0016] Furthermore, the concentration of concentrated sulfuric acid in step S1 is 98wt%, and the mass ratio of concentrated sulfuric acid to potassium permanganate is 1:0.02-0.05.
[0017] Furthermore, in step S2, the mass ratio of graphene oxide to silane coupling agent is 10-50:1.
[0018] Furthermore, the silane coupling agent is one or more of KH-550, KH-560 and KH-570.
[0019] Furthermore, in step S3, the weight ratio of the initiator BPO, 1-methoxy-2-propanol, chain transfer agent and triethanolamine is 0.1-3:30-100:5-20:10-50, and the mass ratio of the 1-methoxy-2-propanol to the mixed solution is 3-10:100-170.
[0020] Furthermore, the chain transfer agent is one or more of acetone, isopropanol, and sodium bisulfite.
[0021] Furthermore, the amount of organosilicon-modified graphene oxide used is 1-5% of the acrylic acid solution.
[0022] In the step of preparing graphene oxide from graphite in the present application, graphite and sodium nitrate are oxidized by potassium permanganate in the presence of concentrated sulfuric acid to generate graphene oxide with a two-dimensional structure and containing a large number of oxygen-containing functional groups, and its abundant oxygen-containing functional groups can be used as connection points to chemically react with silane coupling agents to achieve surface modification. Next, graphene oxide is modified by silane coupling agents, which is a key step to improve the performance of acrylic coatings. Silane coupling agents can introduce organic functional groups on the surface of graphene oxide, and these functional groups can form covalent bonds with acrylate monomers to build a stable three-dimensional network structure. This structure can not only enhance the mechanical properties of composite materials, such as impact resistance and wear resistance, but also improve the weather resistance and waterproof properties of coatings. Silicone-modified graphene oxide can effectively block the direct effects of ultraviolet rays and reduce the aging rate of the coating; at the same time, due to the hydrophobicity of the silane coupling agent, the penetration of water into the interior of the coating can be significantly reduced, thereby improving the waterproof ability of the coating. In addition, the introduction of silane coupling agent also helps to improve the adhesion between the coating and the substrate, ensuring that the coating can maintain good bonding properties under various environmental conditions. Subsequently, in step S3, the modified graphene oxide is copolymerized with hydroxy acrylate monomers by free radical polymerization to form a composite emulsion. In this process, dibenzoyl peroxide is used as an initiator to decompose and produce free radicals at a certain temperature, triggering the polymerization reaction of the monomer. The selection of monomers such as methyl methacrylate, acrylic acid, hydroxyethyl methacrylate, styrene and butyl acrylate is to balance the hardness, flexibility and chemical resistance of the coating. By precisely controlling the proportion of each component and the polymerization conditions, a composite emulsion with excellent mechanical properties and stability can be obtained. It is worth noting that the use of chain transfer agents can regulate the molecular weight of the polymer to avoid excessive molecular weight resulting in excessive viscosity of the coating, which affects the construction performance. The composite emulsion finally formed not only has a high solid content, but also has good fluidity and coating properties, and is suitable for various coating methods. DETAILED DESCRIPTION
[0023] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.
[0024] The equipment used in the preparation method of the present invention can be the well-known equipment in the art. The raw materials used in the present invention are commercially available unless otherwise specified.
[0025] Example 1
[0026] S1. After mixing graphite and sodium nitrate in a mass ratio of 2:1, slowly add 120 mL of 98% concentrated sulfuric acid, then place in a 0±1°C ice-water mixture and stir, slowly add 12 g of potassium permanganate and stir at 35°C for 10 h, then add deionized water for dilution, slowly stir and drop 40% hydrogen peroxide until the solution turns golden yellow, then let stand for 10 h, then filter the solution, wash with 15% hydrochloric acid to a pH of 7, then wash the solution with deionized water and dry to obtain graphene oxide;
[0027] S2, adding 45 mL of deionized water to the graphene oxide obtained in S1 and mixing evenly, adding 3 g of silane coupling agent to anhydrous ethanol to dissolve, and then adding to the aqueous solution of graphene oxide, followed by ultrasonic treatment and stirring; adding hydrochloric acid and adjusting the pH to 7, reacting in a 50° C. water bath for 2 hours, then heating to 80° C. to continue the reaction, finally cooling to room temperature, centrifuging, washing, and drying to obtain organosilicon-modified graphene oxide;
[0028] S3, 0.1g initiator BPO and 100g 1-methoxy-2-propanol were mixed and heated to 100°C, 5g chain transfer agent isopropanol was added, and then a mixed solution of 300g methyl methacrylate, 200g acrylic acid, 100g hydroxyethyl methacrylate and 500g styrene was added dropwise within 3h, and the mixture was kept warm for 1h, and then 30g organosilicon-modified graphene synthesized in S2 was added at 120°C, and then kept warm for 2h, cooled to 70°C, 40g triethanolamine was added and reacted for 40min, and then 100mL deionized water was added to disperse the mixture to obtain an acrylic coating;
[0029] S4. Apply the acrylic paint obtained in S3 onto a polytetrafluoroethylene film-forming plate, and then dry it at room temperature for 7 days to form a film naturally. Put it in an oven and dry it at 60° C. for 48 hours to form a film.
[0030] Example 2
[0031] S1. After mixing graphite and sodium nitrate in a mass ratio of 5:1, slowly add 120 mL of 98% concentrated sulfuric acid, then place in a 0±1°C ice-water mixture and stir, slowly add 8 g of potassium permanganate and stir at 33°C for 8 hours, then add deionized water for dilution, slowly stir and drop 30% hydrogen peroxide until the solution turns golden yellow, then let stand for 8 hours, then filter the solution, wash with 10% hydrochloric acid to a pH of 6, then wash the solution with deionized water and dry to obtain graphene oxide;
[0032] S2, adding 40 mL of deionized water to the graphene oxide obtained in S1 and mixing evenly, adding 1 g of silane coupling agent to anhydrous ethanol to dissolve, and then adding to the aqueous solution of graphene oxide, followed by ultrasonic treatment and stirring; adding hydrochloric acid and adjusting the pH to 5, reacting in a 48° C. water bath for 1 hour, then heating to 70° C. to continue the reaction, finally cooling to room temperature, centrifuging, washing, and drying to obtain organosilicon-modified graphene oxide;
[0033] S3, 1g initiator BPO and 30g 1-methoxy-2-propanol were mixed and heated to 120°C, 30g chain transfer agent acetone was added, and then a mixed solution of 500g methyl methacrylate, 300g acrylic acid, 200g hydroxyethyl methacrylate and 400g styrene was added dropwise within 3h, and the mixture was kept warm for 0.5h, and then 10g organosilicon-modified graphene synthesized by S2 was added at 120°C, and then kept warm for 1.5h, cooled to 70°C, 20g triethanolamine was added and reacted for 20min, and then 500mL deionized water was added to disperse the mixture to obtain an acrylic coating;
[0034] S4. Apply the acrylic paint obtained in S3 onto a polytetrafluoroethylene film-forming plate, and then dry it at room temperature for 7 days to form a film naturally. Put it in an oven and dry it at 50° C. for 36 hours to form a film.
[0035] Example 3
[0036] S1. After mixing graphite and sodium nitrate in a mass ratio of 1:1, slowly add 120 mL of 98% concentrated sulfuric acid, then place in a 0±1°C ice-water mixture and stir, slowly add 15 g of potassium permanganate and stir at 37°C for 10 h, then add deionized water for dilution, slowly stir and drop 50% hydrogen peroxide until the solution turns golden yellow, then let stand for 12 h, then filter the solution, wash with 20% hydrochloric acid to a pH of 6, then wash the solution with deionized water and dry to obtain graphene oxide;
[0037] S2, adding 50 mL of deionized water to the graphene oxide obtained in S1 and mixing evenly, adding 5 g of silane coupling agent to anhydrous ethanol to dissolve, and then adding to the aqueous solution of graphene oxide, followed by ultrasonic treatment and stirring; adding hydrochloric acid and adjusting the pH to 6, reacting in a 52° C. water bath for 2 hours, then heating to 75° C. to continue the reaction, finally cooling to room temperature, centrifuging, washing, and drying to obtain organosilicon-modified graphene oxide;
[0038] S3, 2g initiator BPO and 20g 1-methoxy-2-propanol were mixed and heated to 120°C, 30g chain transfer agent acetone was added, and then a mixed solution of 400g methyl methacrylate, 200g acrylic acid, 200g hydroxyethyl methacrylate and 500g styrene was added dropwise within 3h, and the mixture was kept warm for 0.5h, and then 15g organosilicon-modified graphene synthesized by S2 was added at 120°C, and then kept warm for 2h, cooled to 70°C, 30g triethanolamine was added and reacted for 20min, and then 400mL deionized water was added to disperse the mixture to obtain an acrylic coating;
[0039] S4. Apply the acrylic paint obtained in S3 onto a polytetrafluoroethylene film-forming plate, and then dry it at room temperature for 7 days to form a film naturally. Put it in an oven and dry it at 50° C. for 36 hours to form a film.
[0040] Comparative Example 1
[0041] S1. After mixing graphite and sodium nitrate in a mass ratio of 2:1, slowly add 120 mL of 98% concentrated sulfuric acid, then place in a 0±1°C ice-water mixture and stir, slowly add 12 g of potassium permanganate and stir at 35°C for 10 h, then add deionized water for dilution, slowly stir and drop 40% hydrogen peroxide until the solution turns golden yellow, then let stand for 10 h, then filter the solution, wash with 15% hydrochloric acid to a pH of 7, then wash the solution with deionized water and dry to obtain graphene oxide;
[0042] S2, 1g initiator BPO and 30g 1-methoxy-2-propanol were mixed and heated to 100°C, 10g chain transfer agent isopropanol was added, and then a mixed solution of 300g methyl methacrylate, 200g acrylic acid, 100g hydroxyethyl methacrylate and 500g styrene was added dropwise within 3h, and the mixture was kept warm for 1h, and then 30g graphene oxide obtained in S1 was added at 120°C, and then kept warm for 2h, cooled to 70°C, 40g triethanolamine was added and reacted for 40min, and then 100mL deionized water was added to disperse the mixture to obtain an acrylic coating;
[0043] S4. Apply the acrylic paint obtained in S3 onto a polytetrafluoroethylene film-forming plate, and then dry it at room temperature for 7 days to form a film naturally. Put it in an oven and dry it at 60° C. for 48 hours to form a film.
[0044] Comparative Example 2
[0045] S1. Mix 1g of dibenzoyl peroxide and 30g of 1-methoxy-2-propanol and heat to 120°C, add 10g of chain transfer agent isopropanol, then drop a mixed solution of 300g of methyl methacrylate, 200g of acrylic acid, 100g of hydroxyethyl methacrylate and 600g of styrene within 3h, then keep the mixture warm for 2h, cool to 65°C, add 20g of triethanolamine and react for 20min, then add 500mL of deionized water to disperse the mixture to obtain an acrylic paint;
[0046] S2. Apply the acrylic paint obtained in S1 onto a polytetrafluoroethylene film-forming plate, dry it at room temperature for 7 days to form a film naturally, and put it into an oven and dry it at 60° C. for 48 hours to form a film.
[0047] Comparative Example 3
[0048] S1. After mixing graphite and sodium nitrate in a mass ratio of 2:1, slowly add 120 mL of 98% concentrated sulfuric acid, then place in a 0±1°C ice-water mixture and stir, slowly add 12 g of potassium permanganate and stir at 35°C for 10 h, then add deionized water for dilution, slowly stir and drop 40% hydrogen peroxide until the solution turns golden yellow, then let stand for 10 h, then filter the solution, wash with 15% hydrochloric acid to a pH of 7, then wash the solution with deionized water and dry to obtain graphene oxide;
[0049] S2, adding 45 mL of deionized water to the graphene oxide obtained in S1 and mixing evenly, adding 3 g of silane coupling agent to anhydrous ethanol to dissolve, and then adding to the aqueous solution of graphene oxide, followed by ultrasonic treatment and stirring; adding hydrochloric acid and adjusting the pH to 7, reacting in a 50° C. water bath for 2 hours, then heating to 80° C. to continue the reaction, finally cooling to room temperature, centrifuging, washing, and drying to obtain organosilicon-modified graphene oxide;
[0050] S3, 0.1g initiator BPO and 100g 1-methoxy-2-propanol were mixed and heated to 100°C, 5g chain transfer agent isopropanol was added, and then a mixed solution of 300g methyl methacrylate, 200g acrylic acid, 100g hydroxyethyl methacrylate and 500g styrene was added dropwise within 3h, and the mixture was kept warm for 1h, and then 50g organosilicon-modified graphene synthesized in S2 was added at 120°C, and then kept warm for 2h, cooled to 70°C, 40g triethanolamine was added and reacted for 40min, and then 100mL deionized water was added to disperse the mixture to obtain an acrylic coating;
[0051] S4. Apply the acrylic paint obtained in S3 onto a polytetrafluoroethylene film-forming plate, and then dry it at room temperature for 7 days to form a film naturally. Put it in an oven and dry it at 60° C. for 48 hours to form a film.
[0052] The films obtained in the examples and comparative examples were tested, and the test results are shown in the following table:
[0053]
[0054] The tensile strength and elongation were tested according to GB / T528-1998 standard, and the acid and alkali resistance was tested according to GB / T 13353-92 standard. 10% sulfuric acid solution and 10% sodium hydroxide solution were selected. The samples were soaked for 7 days respectively and then taken out to test the change rate of various mechanical properties.
Claims
1. A method for preparing a high-performance acrylic coating, characterized in that: The following steps are involved: S1. After mixing graphite and sodium nitrate, slowly add concentrated sulfuric acid, then place in an ice-water mixture and stir, slowly add potassium permanganate and stir at 33-37°C for 8-10h, then add deionized water, slowly stir and drop hydrogen peroxide until the solution turns golden yellow, then let stand for 8-12h, then filter the solution, wash with hydrochloric acid until the pH of the solution is 5-7, then wash the solution with deionized water and dry to obtain graphene oxide; S2, adding deionized water to the graphene oxide obtained in S1 and mixing evenly, adding a silane coupling agent to anhydrous ethanol to dissolve, and then adding it to the aqueous solution of graphene oxide, followed by ultrasonic treatment and stirring; adding hydrochloric acid and adjusting the pH to 5-7, reacting in a 48-52°C water bath for 1-2 hours, then heating to 70-80°C and continuing the reaction for 1-2 hours, finally cooling to room temperature, centrifuging, washing, and drying to obtain organosilicon-modified graphene oxide; S3, mixing initiator BPO and 1-methoxy-2-propanol and heating to 100-120°C, adding a chain transfer agent, and then dripping a mixed solution of methyl methacrylate, acrylic acid, hydroxyethyl methacrylate, and styrene, dripping within 3 hours, keeping warm for 0.5h-1h, then adding the organosilicon-modified graphene synthesized in S2 at 100-120°C, and then keeping warm for 1.5-2h, cooling to 65-70°C, adding triethanolamine to react for 20-40min, and then adding deionized water to disperse to obtain an acrylic coating; S4. Apply the acrylic paint obtained in S3 onto a polytetrafluoroethylene film-forming plate, and then dry it at room temperature for 5-7 days to form a film naturally, and put it into an oven and dry it at 50-60° C. for 36-48 hours to form a film.
2. The method for preparing the high performance acrylic paint according to claim 1, characterized in that: The mass ratio of graphite to sodium nitrate in step S1 is 1-5:
1.
3. The method for preparing the high performance acrylic paint according to claim 1, characterized in that: The concentration of concentrated sulfuric acid in step S1 is 98wt%, and the mass ratio of concentrated sulfuric acid to potassium permanganate is 1:0.02-0.
05.
4. The method for preparing the high performance acrylic paint according to claim 1, characterized in that: The mass ratio of graphene oxide to silane coupling agent in step S2 is 10-50:
1.
5. The method for preparing the high performance acrylic paint according to claim 4, characterized in that: The silane coupling agent is one or more of KH-550, KH-560 and KH-570.
6. The method for preparing the high performance acrylic paint according to claim 1, characterized in that: In step S3, the weight ratio of the initiator BPO, 1-methoxy-2-propanol, chain transfer agent and triethanolamine is 0.1-3:30-100:5-20:10-50, and the mass ratio of the 1-methoxy-2-propanol to the mixed solution is 3-10:100-170.
7. The method for preparing the high performance acrylic paint according to claim 1, characterized in that: In the mixed solution of step S3, the mass ratio of methyl methacrylate, acrylic acid, hydroxyethyl methacrylate and styrene is 30:20:10:40-50:40:20:
60.
8. The method for preparing the high performance acrylic paint according to claim 1, characterized in that: The chain transfer agent is one or more of acetone, isopropanol and sodium bisulfite.
9. The method for preparing the high performance acrylic paint according to claim 1, characterized in that: The amount of the organosilicon-modified graphene oxide used in step S3 is 1-5% of the mass of the acrylic acid.
10. A high performance acrylic paint, characterized in that: The high-performance acrylic coating is prepared according to the preparation method of any one of claims 1 to 8.
Citation Information
Patent Citations
Modified graphene oxide / polyacrylate nano composite coating and preparation method thereof
CN107652817A
Polyacrylate latex and preparation method thereof
CN109554045A
Modified graphene oxide / acrylic resin composite anticorrosive paint as well as preparation and application thereof
CN110003751A
Graphene oxide modified waterborne acrylic coating and preparation method thereof
CN112300652A
Road marking paint composition with high flexibility and high durability
KR102365737B1